Efficacy of Deepana-Pachana, Swedana and Shamana Chikitsa in Juvenile Idiopathic Arthritis (JIA) (AYUSHDHARA, 2023)
Juvenile Idiopathic Arthritis (JIA) is a type of most common chronic inflammatory rheumatic disease with very little clarity about etiology and pathology. Main clinical findings: A 16-year-old adolescent female girl with the complaint of pain and swelling in knee joint bilaterally, difficulty in walking, restricted movement and pain in wrist, ankle and interphalangeal joints, morning stiffens in hand and wrist joints. Diagnosis: This case of Juvenile Polyarticular (RF positive) arthritis was diagnosed as Amavata (symptoms suggest pravridhavastha). Interventions: Treatment given for 3 months in a duration dependent pattern. Deepana, Pachana followed by Snehan, Rechana and Baluka sweda, Upnah was done along with oral medications. Outcome:  Patient felt relief in pain, swelling of joints reduced, restriction of joint movement was reduced, Lakshana of Ama like Anorexia, Fatigue, Heaviness and Laziness were also relieved. Conclusion: This paper is an attempt to explore effectiveness of Ayurvedic treatment in case of JIA.